ESTIMASI KEMAMPUAN BERPIKIR KRITIS MAHASISWA PENDIDIKAN PROFESI GURU (PPG) BAGI GURU MADRASAH DAN PENDIDIKAN AGAMA ISLAM PADA MODUL EVALUASI PEMBELAJARAN - Lian Gafar Otaya (Irfani (e-Journal), 2023)
This study aimed to estimate the critical thinking abilities of In-service PPG students for madrasah and religion teachers under the Ministry of Religion of the Republic of Indonesia in enhancing the Learning Evaluation module content at LPTK IAIN Sultan Amai Gorontalo. The subjects of the study were 251 PPG Batch 3 2022 students. The data acquisition method utilized an essay-formatted written examination. The data analysis implemented the Item Response Theory (IRT) approach, the Graded Response Model (GRM). The estimation results of PPG students' critical thinking ability parameters indicated that PPG students had an ability (θ) between –3 and +3, according to the origin of the normal distribution, which was determined by the item difficulty level parameter, indicating that higher critical thinking skills are required to achieve higher value categories when studying the Learning Evaluation module